PENGARUH KETERLIBATAN KERJA TERHADAP PERFORMA KERJA DENGAN KOMITMEN ORGANISASIONAL SEBAGAI PEMEDIASI PADA PT. BANK ACEH KANTOR PUSAT OPERASIONAL BANDA ACEH - Jufriadi, Fairuzzabadi (Departemen Manajemen, 2017)
This study aimd to determine the effect of job involvement to job performance with organizational commitment as a mediating. The empirical study conducted at PT. Bank Aceh The Operational Banda Aceh staff used a questionnaire as a research instrument, which samples in this study of 120 samples. Probability sampling is used as a sampling technique with Total Smpling. Methods HLM (Hierarchical Linear Modelling) is used as a method of data analysis using software IBM SPSS 20. These results indicate that the job involvement significant impact on job performance, job involvement significantly related to organizational commitment, work motivation organizational commitment significant impact on job performance and in addition showed that the organizational commitment mediates the significantly effect of job involvement to job performance.